1989
DOI: 10.1227/00006123-198902000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Unilateral Hydrocephalus in Adults

Abstract: Unilateral dilatation of the lateral ventricle in adults is rare. We report 2 cases of unilateral hydrocephalus with obstruction at the foramen of Monro. Both patients presented with symptoms of raised intracranial pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…8) Total congenital occlusion of the foramen of Monro is uncommon and usually occurs in infants or children. 16,19,22) Idiopathic occlusion of both foramina of Monro is extremely rare in adults, with only three cases of idiopathic occlusion of bilateral 10,11) and seven cases of unilateral 9,17,21) foramen of Monro reported. The usual treatment is either open microsurgical reconstruction of the foramen of Monro, or ventriculoperitoneal or ventriculoatrial shunting.…”
Section: Introductionmentioning
confidence: 99%
“…8) Total congenital occlusion of the foramen of Monro is uncommon and usually occurs in infants or children. 16,19,22) Idiopathic occlusion of both foramina of Monro is extremely rare in adults, with only three cases of idiopathic occlusion of bilateral 10,11) and seven cases of unilateral 9,17,21) foramen of Monro reported. The usual treatment is either open microsurgical reconstruction of the foramen of Monro, or ventriculoperitoneal or ventriculoatrial shunting.…”
Section: Introductionmentioning
confidence: 99%
“…Placement of a shunt of CSF diversion from the dilated ventricle has been suggested by some [8,13]. Fenestration of the septum pellucidum by open craniotomy was performed in 14 patients in a study reported by Mampalam et al [1].…”
Section: Discussionmentioning
confidence: 99%
“…Acquired obstruction of the foramen of Monro is com moner and can occur due to tumors at or near the foramen Unilateral Hydrocephalus Pediatr Ncurosurg 1996;25:248-251 of Monro [1], cysticercus cysts [17], vascular malforma tion [2,3], post-inflammatory gliosis [4] or as a conse quence of shunt placement in the contralateral ventricle [5,10]. Congenital atresia of the foramen of Monro is rela tively rare and mostly occurs in infants or young children [6-8, 10, 11], However, a few reports mention its occur rence in adulthood [1,9,12,13]. Some of the cases of unilateral hydrocephalus due to congenital atresia of the foramen of Monro have been associated with congenital ventricular diverticulum [7,11], Usually manifesting as progressive enlargement of the head in children and raised intracranial pressure in adults, this uncommon condition is well diagnosed by a CT scan or MR1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AV malformation of the choroid plexus (4,14), and basilar artery aneurysm or ectasia (7)), or iatrogenic complications. Idiopathic occlusion of foramen of Monro, a situation in which no clue can be detected to the etiology of foraminal obstruction, is an extremely rare phenomenon in adults with only five cases of bilateral and ten cases of unilateral obstruction reported in the literature (6,(10)(11)(12)(13)15). …”
Section: Introductionmentioning
confidence: 99%